Uma análise empírica do spread das companhias do setor de óleo e gás - Almeida, Guilherme Ribeiro de (2010)
In this paper, we use the information from the credit default swap market to measure the main components of the oil and gas companies spread. Using nearly 20 companies of this industry with different ratings and nearly 80 bonds, the result was that the majority of the oil and gas spread is due to the default risk. We also find that the spread component related to the non-default is strongly as sociated with some liquidity measures of bond markets, what suggest that liquidity has a very important role in the valuation of fixed income assets. On the other side, we do not find evidence that the non-default component of the spread is related to tax matters.